Genomic Differences and Distinct TP53 Mutation Site‐Linked Chemosensitivity in Early‐ and Late‐Onset Gastric Cancer - Tomohiro Kamio; Yoshiyasu Kono; Kensuke Hirosuna; Toshiki Ozato; Hideki Yamamoto; Akira Hirasawa; Daisuke Ennishi; Shuta Tomida; Shinichi Toyooka; Motoyuki Otsuka (Cancer Medicine)
ABSTRACT Background Gastric cancer (GC) in younger patients often exhibits aggressive behavior and a poorer prognosis than that in older patients. Although the clinical differences may stem from oncogenic gene variations, it is unclear whether genetic differences exist between these groups. This study compared the genetic profiles of early‐ and late‐onset GC and evaluated their impact on treatment outcomes. Methods We analyzed genetic data from 1284 patients with GC in the Japanese nationwide Center for Cancer Genomics and Advanced Therapeutics (C‐CAT) database, comparing early‐onset (≤ 39 years; n = 143) and late‐onset (≥ 65 years; n = 1141) groups. The influence of TP53 mutations on the time to treatment failure (TTF) with platinum‐based chemotherapy and the sensitivity of cancer cells with different TP53 mutation sites to oxaliplatin were assessed in vitro. Results Early‐ and late‐onset GC showed distinct genetic profiles, with fewer neoantigen‐associated genetic changes observed in early‐onset cases. In particular, TP53 has distinct mutation sites; R175H and R273 mutations are more frequent in early‐ and late‐onset GC, respectively. The R175H mutation showed higher sensitivity to oxaliplatin in vitro, consistent with the longer TTF in early‐onset patients (17.3 vs. 7.0 months, p = 0.013) when focusing on the patients with TP53 mutations. Conclusion Genomic differences, particularly in TP53 mutation sites, between early‐ and late‐onset GC support the need for age‐specific treatment strategies.